PENGARUH BEBAN KERJA, PENERAPAN SISTEM PENGUKURAN KERJA, DAN PENGHARGAAN TERHADAP KINERJA PEGAWAI (STUDI PADA BANK JATENG KANTOR PUSAT SEMARANG) - Nastiti Wiharrani, 11.05.51.0064 (Students Journal of Economic and Management, 2015)
This study examines the effect of workload, work measurement system implementation and employee performance awards research was conducted in Central Java Bank Head Office. The sampling method used purposive sampling and number of samples taken based on the opinion Sugiyono (2010) which states that the number of samples using Slovin formula of 189 respondents. Relationship and or influence between variables is described by multiple regression analysis method. The results showed that the workload, work measurement system application and award positive and significant impact on employee performance. So, if the workload, the application of work measurement and reward systems for the better, it will be a better performance resulting employee Keywords: Workload, Work Measurement Ssystem Implementation and Employee Performance